Testing of a Device for Positioning Measuring Microphones in Anechoic and Reverberation Chambers - FELIS, Józef; FLACH, Artur; KAMISIŃSKI, Tadeusz (Archives of Acoustics, 2012)
This paper presents a mechanical positioning system for a measuring microphone designed for acoustic studies in anechoic and reverberation chambers at the Department of Mechanics and Vibroacoustics, AGH. The results are discussed in the context of mechanical positioning and its impact on the outcome of the execution of individual measurement procedures. Moreover, areas for research were identified and solution concepts shown for further development of the automation of acoustic measurements in different research rooms in order to reduce the human involvement in them.